GAMBARAN UMUM GAYA BERJALAN PADA LANJUT: GAMBARAN UMUM GAYA BERJALAN PADA LANJUT - Puspita, Putu Ayu Diah; Saraswati, Putu Ayu Sita; Negara, Anak Agung Gede Angga Puspa (PT. Kesehatan Gerak Fungsi Tubuh, 2023)
Background: One of the most affected functional movements in the elderly due to aging is gait. Several parameters must be considered when conducting a gait analysis, including stride speed, length, width, and variability. This study aimed to provide an overview of gait in the elderly group. Methods: The research method used was a literature review in the form of a literature review, compiled based on secondary data from several research journals related to gait in the elderly. This Literature Review contains journals from databases such as Google Scholar and PubMed. Results: Through the elaboration of several studies comparing the elderly group with younger individuals, it could be seen that three aspects influence gait in the elderly, namely sensory, cognitive, and musculoskeletal. Conclusion: The elderly have a loss in sensory, cognitive, and musculoskeletal function as they age, resulting in slower and shorter stride lengths when compared to younger people.